Asosiasi Diferensial dan Pembunuhan: Eksplorasi Sosiologis Terhadap Motif dan Dampak Kasus Dukun Pengganda Uang di Banjarnegara - Diva Kayla Nazwa Anas; Faridah Faridah; Ghazy Aldifa Afti; Nindia Monita Br Ginting; Vinsensia Carolin Purba (Pusat Riset dan Inovasi Nasional, 2023)
This research discusses the motives and impacts of the murder of a money-making shaman in Banjarnegara using sociological analysis. The method used is a qualitative approach with literature review. This case was analyzed using Sutherland's Differential Association theory. The results of the research show that the murder case of a money-making shaman in Banjarnegara is an action that can be studied by the techniques and methods of criminal acts. Also, before the criminal act occurs, there is a process of interpreting the profits and losses by the perpetrator.